Changes in lung cancer-related serum tumor markers in patients with chronic kidney disease and determination of upper reference limit - Miao, Qiang; Cai, Bei; Niu, Qian; Zhang, Junlong (Frontiers in Oncology, 2022)
Aims To investigate the changes in lung cancer-related serum tumor markers in patients with chronic kidney disease (CKD) and determine the upper reference limit for patients with different stages. Methods Included inpatients diagnosed with CKD who did not receive dialysis temporarily in our hospital from March to September 2020. Changes in serum CA125, HE4, CYFRA21-1, SCCA, NSE and ProGRP in CKD patients were analyzed. The non-parametric method was used to estimate the upper reference limit of the above indicators in patients with CKD stages 2-5. Results The serum levels of HE4, CYFRA21-1, SCCA, and ProGRP in the CKD group were significantly higher than those in the healthy control group; CA125 and NSE levels were not statistically different. The false positives of SCC, CYFRA21-1, ProGRP, and HE4 increased significantly with the CKD stage. Still, NSE and CA125 did not show a significant increasing trend. Both HE4 and ProGRP have independent upper reference limits from CKD2 to CKD5 stage, namely 220.8 pmol/l and 101.4 pg/ml in the CKD2 stage, 496.7 pmol/l and 168.63 pg/ml in CKD3 stage, 4592.4 pmol/l and 272.8 pmol/l for CKD4 stage, CKD5 stage was 4778.2 pmol/l and 491.6 pmol/l. Conclusion This study preliminarily determined the upper reference limits of Lung cancer-related tumor markers in patients with different CKD stages and provided laboratory support for the rational use and interpretation of Lung cancer-related tumor markers in special populations.